Reconfiguring Justice: Judicial Discretion and the Validation of Underage Marriages in the Modern Era - Khotimah, Khusnul; Ahmad, Sabarudin; Suriansyah, Eka (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research examine the legal reasoning of the judge in Supreme Court decision Number 481 K/Ag/2021 after being declared unacceptable determination or N.O (Niet Ontvankelijk verklaart) in Ujung Tanjung Religious Court Order Number 14/Pdt.P/2021/PA.Utj. This research aims to find out the legal reasoning of the judge in granting the appeal for cassation of underage marriage isbat in Supreme Court Decision Number 481 K/Ag/2021 and analyzing from Islamic law review. The type of research used in this research is normative legal research with a statutory approach and a case approach. This research examines and studies various literature sourced from secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The method of analysis used is descriptive analytical. The results in this study show: (1) The judge in his decision has applied freedom in examining and deciding cases, in Supreme Court Decision No. 481 K/Ag/2021 the judge considered that the petitioners had fulfilled the conditions and pillars of marriage according to Islamic law, and for the sake of legal certainty and protection, the judge felt that there were sufficient reasons to grant the cassation request. (2) The judge has fulfilled the purpose of maṣlaḥah, which is to maintain primary needs or maintenance of basic human elements in accordance with the objectives to be achieved in maṣlaḥah ḍarūriyah.